2014
DOI: 10.1016/j.rgmx.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Nivel de proteína C reactiva en pacientes con obesidad mórbida antes y después de cirugía bariátrica

Abstract: Preoperative CRP had a significant lineal relation to weight and body mass index. Patients who underwent bariatric surgery had a significant decrease in CRP, weight, and fasting glucose at 6 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Overall, several parameters determined in our patient cohort were comparable to already established results from bariatric surgery patients including a massive drop of BMI, change in lipid profile including a drop in LDL and an increase in HDL and a reduction in inflammatory markers IL-6 and CRP and the prothrombotic protein PAI-1 [20, 21]. Similar drops in weight and CRP levels were also described in a Mexican cohort of bariatric surgery patients [22]. The overall amelioration of obesity was further met by a reduction in medication needed.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, several parameters determined in our patient cohort were comparable to already established results from bariatric surgery patients including a massive drop of BMI, change in lipid profile including a drop in LDL and an increase in HDL and a reduction in inflammatory markers IL-6 and CRP and the prothrombotic protein PAI-1 [20, 21]. Similar drops in weight and CRP levels were also described in a Mexican cohort of bariatric surgery patients [22]. The overall amelioration of obesity was further met by a reduction in medication needed.…”
Section: Discussionsupporting
confidence: 85%
“…Multiple studies have reported a decrease in CRP levels, a frequently assessed marker of systemic inflammation in the clinical setting after bariatric surgery. CRP has been shown to decrease from 1.15 to 0.34 mg/l at 6 months after either RYGB or LSG in a small cohort of Mexican subjects [63]. CRP was also found to fall from 0.68 to 0.55 mg/dl 3 months after LAGB, associated with a 13.9% weight loss, in 46 subjects [64].…”
Section: Bariatric Surgery Is Associated With a Decrease In Systemmentioning
confidence: 99%
“…C‐reactive protein (CRP), an important inflammatory marker in serum, has been reported to be elevated in persons who are obese, and correlates with insulin resistance and endothelial dysfunction. 2 Obesity or an increase of fatty tissue causes chronic inflammation in the body, which in turn causes an increase in cytokine synthesis. 3 The level of CRP in blood at an acute stage is an early marker of inflammation or infection, and has been associated with central obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they suffer from a low‐grade chronic proinflammatory state, which is the factor that links endothelial dysfunction to insulin resistance and obesity. C‐reactive protein (CRP), an important inflammatory marker in serum, has been reported to be elevated in persons who are obese, and correlates with insulin resistance and endothelial dysfunction 2 . Obesity or an increase of fatty tissue causes chronic inflammation in the body, which in turn causes an increase in cytokine synthesis 3 .…”
Section: Introductionmentioning
confidence: 99%